What makes the maternal X chromosome resistant to undergoing imprinted X inactivation?. (25th September 2017) - Sado, Takashi
Abstract : In the mouse, while either X chromosome is chosen for inactivation in a random fashion in the embryonic tissue, the paternally derived X chromosome is preferentially inactivated in the extraembryonic tissues. It has been shown that the maternal X chromosome is imprinted so as not to undergo inactivation in the extraembryonic tissues. X-linked noncoding Xist RNA becomes upregulated on the X chromosome that is to be inactivated. An antisense noncoding RNA, Tsix, which occurs at the Xist locus and has been shown to negatively regulate Xist expression in cis, is imprinted to be expressed from the maternal X in the extraembryonic tissues. Although Tsix appears to be responsible for the imprint laid on the maternal X, those who disagree with this idea would point out the fact that Tsix has not yet been expressed from the maternal X when Xist becomes upregulated on the paternal but not the maternal X at the onset of imprinted X-inactivation in preimplantation embryos. Recent studies have demonstrated, however, that there is a prominent difference in the chromatin structure at the Xist locus depending on the parental origin, which I suggest might account for the repression of maternal Xist in the absence of maternal Tsix at the preimplantation stages. This article is part of the themed issue 'X-chromosome inactivation: a tribute to Mary Lyon'.